Kepercayaan Diri Siswa Kelas XI Yang Mengalami Prokrastinasi Akademik di SMA Negeri 2 Lubuklinggau - Hasanah, Ratu Ayu; Hakim, Imam B (Jurnal Konseling Komprehensif: Kajian Teori dan Praktik Bimbingan dan Konseling, 2017)
The aimed of this study was to find out the students self confidence of XI class who faced academic procrastination in SMA Negeri 2 Lubuklinggau. This was survey study and subjects were 32 students who faced academic procrastination. The students self confidence data used psycology likert model scale. The result showed that XI class students who faced/ did the academic procrastination in SMA Negeri 2 Lubuklinggau were in moderate category. It can be stated that the students who had firm belief of ability and positive thinking foward him/ her self well, although not yet fully able to act independently.